A modified A-class fireproof thermal insulation material and preparation method thereof
By using modified insulation materials composed of inorganic microbeads, gelling materials, etc., combined with specific pretreatment and preparation methods, the problem of existing materials being difficult to meet the A-level fire protection and good insulation at the same time, and high-performance building exterior wall insulation materials are achieved.
Patent Information
- Application Number
- CN202411131591.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-16
AI Technical Summary
Existing building exterior wall insulation materials are difficult to meet the A-level fire resistance and good insulation properties at the same time, and are prone to fire, fall off, cracking, and water seepage.
A modified insulation material consisting of inorganic microbeads, gelling materials, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder is used to form a porous structure with Class A fire resistance through specific pretreatment and preparation methods.
The A-level fire resistance of the insulation material is achieved, while maintaining good insulation performance, enhancing the strength, hardness and durability of the material, and avoiding fire and other structural problems.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified composite thermal insulation materials, and in particular to a modified A-class fireproof thermal insulation material and a preparation method thereof. Background Art
[0002] At present, it is mandatory that building insulation and energy-saving materials must meet Class A fireproof standards. At present, the insulation materials used for exterior walls are mainly organic foam boards, which are easy to burn and have a combustion performance level of B1 or B, which is difficult to meet the design requirements of building fireproof performance. With the increasing requirements for energy conservation and emission reduction, energy-saving standards are gradually improving, but the external insulation system of building exterior walls will have more problems such as fire, falling off, cracking, and water seepage.
[0003] At present, since organic thermal insulation materials are flammable and will reduce the fire protection level, it is necessary to reduce the content of organic thermal insulation materials in thermal insulation materials and use more non-combustible inorganic materials.
[0004] Therefore, how to develop a thermal insulation material in which organic thermal insulation materials are reduced or even not used, and on the basis of having Class A fire resistance, the thermal insulation performance is maintained unchanged or not significantly reduced, so that its thermal insulation performance meets the requirements of existing standards, is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] The object of the present invention is to provide a modified A-class fireproof thermal insulation material. Another object of the present invention is to provide a preparation method of the modified A-class fireproof thermal insulation material.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] A modified A-class fireproof thermal insulation material is made of multiple raw materials, including the following raw materials in parts by mass: 20 to 70 parts of inorganic microbeads, 15 to 40 parts of gelling materials, 30 to 50 parts of water, 1 to 8 parts of inorganic whiskers, 8 to 25 parts of aluminum dihydrogen phosphate, 20 to 35 parts of inorganic nanoparticles, 2 to 12 parts of inorganic fibers, and 20 to 50 parts of inorganic aerogel powder.
[0008] Preferably, the inorganic fiber is one, two or more of glass fiber, asbestos fiber, boron fiber, aluminum silicate fiber and ceramic fiber.
[0009] Preferably, the inorganic aerogel powder is one, two or more of SiO2 aerogel, Al2O3 aerogel, TiO2 aerogel, ZrO2 aerogel, Fe2O3-Al2O3 aerogel and Fe2O3-SiO2 aerogel.
[0010] Preferably, the gelling material is an inorganic gelling material and / or an organic gelling material;
[0011] The inorganic gelling material is one, two or more of cement, sodium silicate and silica sol;
[0012] The organic gelling material is organic resin, water-based resin or modified resin.
[0013] Preferably, the pretreatment of the raw materials includes the following steps performed in sequence: in the process of producing inorganic microbeads, one, two or more of inorganic whiskers, inorganic nanoparticles and inorganic aerogel powders are added to the inorganic microbeads when they are about to be expanded, and then the inner hollow cavity of the inorganic microbeads after expansion contains one, two or more of inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles, forming a structure in which particles are contained in beads.
[0014] Preferably, the pretreatment of the raw materials includes the following steps performed in sequence: mixing the inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder uniformly, and then pressing them into a compact, and then placing the compact in a heating furnace for heating and heat preservation for a period of time in an argon atmosphere, during the heating process, the glass fibers are heated and softened, and the adhesiveness and bonding force generated by the heated and softened glass fibers bond the inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fibers, and then during the furnace cooling process, the inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fibers, and then the blank obtained after heating is crushed and ground, and the particle size of the pretreated powder obtained by grinding is controlled to be 10 to 20 times the particle size of the inorganic whiskers, inorganic nanoparticles or inorganic aerogel powder, and the particles of the pretreated powder contain inorganic whisker particles, inorganic nanoparticles, glass fibers and inorganic aerogel particles bonded to each other.
[0015] The method for preparing the modified Class A fireproof thermal insulation material described in any one of the above comprises the following steps performed in sequence:
[0016] 1.1) Mixing: According to the formula, the inorganic microbeads, gelling material, water, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder are stirred and mixed uniformly to obtain a mixed slurry;
[0017] 1.2) The prepared mixed slurry is subjected to mold box pressing or roller pressing, and then solidified and cured, and after completion, a thermal insulation material is obtained.
[0018] The method for preparing the modified Class A fireproof thermal insulation material described in any one of the above comprises the following steps performed in sequence:
[0019] 2.1) Inorganic microbeads, a portion of water, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, glass fibers and inorganic aerogel powder are uniformly mixed, and then poured into a mold for pressing to form a wet-pressed slab. The aluminum dihydrogen phosphate is mixed with water to form a binder. The binder glues the inorganic microbeads, inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder together to form a plate-shaped wet-pressed slab. The wet-pressed slab is then dried to form a dry-pressed slab.
[0020] 2.2) placing the dry pressed slab into a heating furnace and heating and keeping it warm in an argon atmosphere for a period of time, during the heating process, the glass fiber is heated and softened, and the adhesiveness and adhesive force generated by the heated and softened glass fiber bond the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fiber, and then during the furnace cooling process, the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fiber, and after cooling, a semi-finished plate with a porous structure is obtained;
[0021] 2.3) The cementitious material is mixed evenly with the remaining water to form a slurry, and then the slurry is poured into the pores of the porous structure of the semi-finished board. The slurry in the pores of the porous structure of the semi-finished board solidifies, and then curing is performed. During the curing process, the cementitious material bonds and fixes the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles together, and a thermal insulation material is obtained after completion.
[0022] The present application has achieved the following beneficial technical effects:
[0023] In the present application, since the thermal conductivity of inorganic microbeads is 0.015 to 0.060 W / (m·K), the thermal conductivity of inorganic microbeads is relatively low, and the inorganic microbeads are hollow and contain bubbles, which belongs to the porous thermal insulation principle, and the inorganic microbeads provide most of the thermal insulation performance of the thermal insulation material;
[0024] In the present application, due to the addition of inorganic nanoparticles, a modified material that is primarily Class A fireproof and secondary low thermal conductivity and heat preservation, and due to the addition of inorganic aerogel powder, a modified material that is both Class A fireproof and ultra-low thermal conductivity and heat preservation, the traditional thermal insulation material made of inorganic microbeads and gelling materials is modified, so that the combustion performance of the thermal insulation material reaches Class A fireproof, and the thermal insulation performance is not significantly reduced, meets the standard requirements, and meets the use requirements. The thermal conductivity of the thermal insulation material is 0.023-0.050W / (m·K);
[0025] In the present application, the added inorganic whiskers and inorganic fibers are both reinforcing materials, which obviously improve the strength, hardness, tensile strength, compression resistance, bending resistance, durability and other properties of the thermal insulation material, and improve the performance stability and dimensional stability of the thermal insulation material. DETAILED DESCRIPTION
[0026] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention.
[0027] The present application provides a modified Class A fireproof thermal insulation material, which is made of a variety of raw materials, including the following raw materials in parts by mass: 20 to 70 parts of inorganic microbeads, 15 to 40 parts of gelling material, 30 to 50 parts of water, 1 to 8 parts of inorganic whiskers, 8 to 25 parts of aluminum dihydrogen phosphate, 20 to 35 parts of inorganic nanoparticles, 2 to 12 parts of inorganic fibers, and 20 to 50 parts of inorganic aerogel powder.
[0028] In the present application, the inorganic microbeads are one, two or more of hollow glass microbeads, solid glass microbeads, hollow ceramic microbeads, solid ceramic microbeads, vitrified microbeads (closed-cell expanded vitrified microbeads), floating beads, pearl sand and perlite;
[0029] The particle size of the inorganic microbeads is 1 micron to 30 microns.
[0030] In the present application, the gelling material is an inorganic gelling material and / or an organic gelling material;
[0031] The inorganic gelling material is one, two or more of cement, sodium silicate and silica sol. The inorganic gelling material is cement or inorganic glue. The preferred cement is silicate cement or fast-hardening cement. The preferred inorganic glue is glue with a fireproof grade of A.
[0032] The organic gelling material is an organic resin, a water-based resin or a modified resin. Preferably, the organic gelling material is one, two or more of polyurethane, melamine and epoxy resin.
[0033] In one embodiment of the present application, the mass parts of water is 30 to 50 mass parts.
[0034] In the present application, the inorganic whiskers are one, two or more of silicon carbide whiskers, titanium carbide whiskers, aluminum borate whiskers, calcium sulfate whiskers, calcium carbonate whiskers, aluminum silicate whiskers, aluminum oxide whiskers and zinc oxide whiskers.
[0035] In the present application, the inorganic nanoparticles are one, two or more of nano-silicon dioxide, nano-aluminum oxide, nano-graphite, nano-aluminum hydroxide, nano-ferric oxide, nano-calcium carbonate and nano-clay;
[0036] The particle size of the inorganic nanoparticles is 1 nanometer to 100 nanometers.
[0037] In the present application, inorganic fiber is a chemical fiber made from minerals as raw materials, and the main varieties include glass fiber, asbestos fiber, boron fiber, aluminum silicate fiber, ceramic fiber, etc. Glass fiber is made from a variety of ores as raw materials through high-temperature melting, wire drawing, winding, weaving and other processes. The diameter of its monofilament is several microns to more than 20 microns, and each bundle of fiber strands is composed of hundreds or even thousands of monofilaments. Glass fiber is usually used as a reinforcing material in composite materials, electrical insulation material and thermal insulation material, etc. Glass fiber is preferably chopped glass fiber strands or ground glass fiber fibers.
[0038] In this application, aerogel refers to a nano-scale porous solid material formed by replacing the liquid phase in the gel with gas through a sol-gel method using a certain drying method; aerogel is currently the best thermal insulation material in the world. Using the thermal insulation properties of aerogel, a new type of aerogel high-efficiency thermal insulation composite material can be produced, which is used in the field of energy-saving buildings and has good thermal insulation, fire retardant, sound insulation, light transmission and other properties; inorganic aerogel powders include SiO2 aerogel, Al2O3 aerogel, TiO2 aerogel, ZrO2 aerogel, Fe2O3-Al2O3 aerogel, Fe2O3-SiO2 aerogel, etc.
[0039] In one embodiment of the present application, the pretreatment of the raw materials includes the following steps performed in sequence: in the process of producing inorganic microbeads, one, two or more of inorganic whiskers, inorganic nanoparticles and inorganic aerogel powders are added to the inorganic microbeads when they are about to be expanded, and then the inner hollow cavity of the inorganic microbeads after expansion contains one, two or more of inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles, forming a structure in which particles are contained in beads.
[0040] In one embodiment of the present application, technical problem (1): In addition to inorganic microbeads and cementitious materials (cement), multiple types of inorganic materials for modification are added in the present application. Among them, because the particle size of inorganic nanoparticles (1 nanometer to 100 nanometers) and inorganic aerogel powder is too small, it is easy to agglomerate and segregate. In addition, because the particle size of cement particles is about 10 micrometers to 50 micrometers, the particle size difference between the two is large, which makes it difficult for inorganic nanoparticles to be evenly mixed with cement particles, and it is difficult for inorganic nanoparticles to be evenly distributed in cement.
[0041] Furthermore, technical problem (2): In the present application, inorganic microspheres and other raw materials are bonded together by cement and other cementitious materials to form the thermal insulation board. Since cement has poor thermal insulation performance, the amount of cement should be reduced as much as possible. However, if the amount of cement is too little, it will lead to insufficient bonding and loose bonding, which will lead to the problem of insufficient strength of the thermal insulation board and easy breakage. This is a contradiction. How to reduce the amount of cement used to improve thermal insulation performance while strengthening bonding, strengthening connection and improving board strength is the technical problem of the present application;
[0042] To this end, in one embodiment of the present application, the pretreatment of the raw material includes the following steps performed in sequence: the inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder are stirred and mixed uniformly, and then pressed into a green compact, and then the green compact is placed in a heating furnace for heating in an argon atmosphere, the glass fibers are heated and softened during the heating process, and the adhesiveness and adhesive force generated by the heated and softened glass fibers bond the inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fibers, and then during the furnace cooling process, the inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fibers, and then the green compact obtained after heating is crushed and ground, and the particle size of the pretreated powder obtained by grinding is controlled to be 10 to 20 times the particle size of the inorganic whiskers, inorganic nanoparticles or inorganic aerogel powder, and the particles of the pretreated powder contain inorganic whisker particles, inorganic nanoparticles, glass fibers and inorganic aerogel particles bonded and connected to each other;
[0043] Here, preferably, the particle size of the pretreated powder of large particles obtained by pretreatment is 5 microns to 30 microns;
[0044] Here, since glass fiber is a non-crystalline material with no fixed melting point, it is generally believed that the softening temperature of glass fiber is between 650°C and 900°C, so the heating temperature is 650°C-800°C and kept warm for 5-10h, and the preferred heating temperature is 650°C-750°C;
[0045] Here, the core working principle is to utilize the lower softening temperature of glass fiber, heat the glass fiber to make it softened by heat to generate adhesion and bonding force, and then the surrounding inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles tightly squeezed together in the compact are firmly bonded to the glass fiber, and then cooled and solidified on the glass fiber together, that is, the softened glass fiber is used to bond and connect a variety of inorganic particles together, that is, the bonding effect of the softened glass fiber is used to replace the bonding effect of a certain amount of gelling material therein;
[0046] Here, after testing: a mixed compact including only inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles was sintered at a heating temperature of 650°C-800°C. The test results showed that the sintering effect was not good, the connection strength between the particles was not high, and it was easy to break. Therefore, the heating temperature of 650°C-800°C is a low and insufficient temperature for sintering, so the heating and heat preservation for a period of time here is not a common sintering process; furthermore, at the heating temperature of 650°C-800°C, only the glass fiber will soften, and the other inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are all ceramic materials resistant to 1300°C-2000°C, resulting in no softening. Therefore, the connection between different types of particles here is based on and only relies on the connection between the softened and then solidified glass fibers, and no sintering connection is formed between different types of particles during the low-temperature heating process of 650°C-800°C;
[0047] Here, the technical effects of bonding inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to glass fibers by using the bonding property and bonding force generated by heating and softening glass fibers are: first, inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel particles are bonded and connected to each other, and clustered together according to the proportion to form large particles. The large particles with larger particle size can avoid the problems of easy agglomeration and segregation naturally existing in the above-mentioned inorganic nanoparticles, etc., and the large particles with larger particle size become close to the particle size of cement particles, which can avoid the problem of uneven mixing of the above-mentioned inorganic nanoparticles and cement particles, so that the large particles of pretreated powder and the remaining raw cement, inorganic microbeads, etc. can be mixed more evenly;
[0048] Secondly, the bonding effect of the softened glass fiber replaces the bonding effect of a certain amount of cementitious materials, thus reducing the amount of cementitious materials used and improving the thermal insulation performance. However, the bonding strength generated by high-temperature heating at 650℃-800℃ is significantly higher than the bonding strength of cement and other cementitious materials hardened at room temperature with water, and the glass fiber itself is a commonly used reinforcing material. Glass fiber is similar to the steel bars in reinforced concrete. Therefore, the bonding force of the high-temperature heated glass fiber strengthens the bonding and connection, thereby improving the strength, hardness, tensile strength, compression resistance, bending resistance, durability and other properties of the thermal insulation material.
[0049] The present application also provides a method for preparing a modified Class A fireproof thermal insulation material, comprising the following steps performed in sequence:
[0050] 1.1) Mixing: According to the formula, the inorganic microbeads, gelling material, water, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder are stirred and mixed uniformly to obtain a mixed slurry;
[0051] 1.2) The prepared mixed slurry is subjected to mold box pressing or roller pressing, and then solidified and cured, and after completion, a thermal insulation material is obtained.
[0052] The present application provides a method for preparing a modified Class A fireproof thermal insulation material, which specifically includes the following steps:
[0053] (1) Production process of mold box compression molding:
[0054] Circular multiple mold boxes, inject mixed slurry into the mold box → capping and pressing (pressure is 7-20 tons) → rest → demoulding → cutting → packaging → storage;
[0055] (2) Roll forming production process:
[0056] Double crawler laminator heating → pouring mixed slurry → double crawler laminator curing → entering high temperature channel (adjustable temperature drying box) → band saw cutting → trimming → cutting → cooling board → automatic palletizing → finished product packaging → storage;
[0057] (3) Single-piece or multi-piece production process:
[0058] Spread the mixed slurry on the flat mold (the thickness depends on the design requirements) → put a single piece or multiple pieces into the press → demold in 1-5 hours → cut and trim → pack → store;
[0059] (4) Adding production process of enhanced structure (adding metal mesh or organic material mesh):
[0060] Heating by double-crawler laminator → Spreading the first layer of mixed slurry (thickness is set according to requirements) → Laying mesh (the position of the mesh is at 1 / 2 of the product thickness, and can also be set according to design requirements) → Spreading the second layer of mixed slurry (thickness is set according to design requirements) → Curing by double-crawler laminator → Entering the high-temperature channel (adjustable temperature drying box) → Cutting with band saw → Trimming → Automatic palletizing → Finished product packaging → Warehousing;
[0061] (5) Adding the production process of the enhanced structure (adding alkali-resistant glass fiber mesh cloth or adding metal mesh and alkali-resistant glass fiber mesh cloth at the same time):
[0062] Double crawler laminator heating → laying cement base cloth (or alkali-resistant glass fiber mesh cloth) → spreading the first layer of mixed slurry (thickness is set according to requirements) → laying mesh (the position of the mesh is at 1 / 2 of the product thickness, and can also be determined according to design requirements) → spreading the second layer of mixed slurry (thickness is determined according to design requirements) → laying cement base cloth (or alkali-resistant glass fiber mesh cloth) → double crawler laminator curing → entering the high-temperature channel (adjustable temperature drying box) → band saw cutting → trimming → automatic palletizing → finished product packaging → warehousing.
[0063] In the present application, mesh: mesh includes metal mesh (metal mesh treated with hot-dip galvanizing, cold-dip galvanizing, carbon black, fluorocarbon, etc.) and organic material (PVC\PC\PE\ABS\PS, etc.) mesh; mesh includes single-sided flat mesh or mesh with tensioned bars.
[0064] In this application, adding glass fiber as a reinforcing material to the thermal insulation material for fiber reinforcement is a common prior art. In the prior art, glass fiber and other raw materials are usually mixed and then hardened together to obtain a board. In this regard, how to more reasonably use glass fiber as a reinforcing material to reduce the amount of cement used and improve thermal insulation performance, but strengthening bonding, strengthening connection and improving board strength are technical issues of this application;
[0065] To this end, in one embodiment of the present application, a method for preparing a modified Class A fireproof thermal insulation material comprises the following steps performed in sequence:
[0066] 2.1) Inorganic microbeads, a portion of water, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, glass fibers and inorganic aerogel powder are uniformly mixed, and then poured into a mold for pressing to form a wet-pressed slab. The aluminum dihydrogen phosphate is mixed with water to form a binder. The binder glues the inorganic microbeads, inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder together to form a plate-shaped wet-pressed slab. The wet-pressed slab is then dried to form a dry-pressed slab.
[0067] 2.2) placing the dry pressed slab into a heating furnace and heating it in an argon atmosphere (preferably heating to 650°C-800°C and keeping the temperature for 5-10 hours), wherein the glass fiber is heated and softened during the heating process, and the adhesiveness and adhesive force generated by the heated and softened glass fiber bond the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fiber, and then during the furnace cooling process, the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fiber, and after cooling, a semi-finished plate with a porous structure is obtained;
[0068] 2.3) The gelling material is mixed with the remaining water to form a slurry, and then the slurry is poured into the pores of the porous structure of the semi-finished plate. The slurry in the pores of the porous structure of the semi-finished plate is solidified, and then curing is performed. During the curing process, the gelling material bonds and fixes the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles together, and a thermal insulation material is obtained after completion;
[0069] Here, the core working principle is: first, the aluminum dihydrogen phosphate in the formula is added with water to form a binder, and all other inorganic raw materials except the cementitious material are bonded together to form a wet pressed slab;
[0070] Then, heating and firing are performed. Similarly, inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded together by softened glass fibers to form a plate. The process of first bonding into a wet pressed slab and then heating and firing to form a plate is similar to the brick-making process in the prior art.
[0071] Since the inorganic microbeads, inorganic nanoparticles and inorganic aerogel powders are all in the form of particles with their own particle sizes, naturally, there are a large number of naturally existing and inevitable pores between adjacent particles in the wet pressed blank, the dry pressed blank and the semi-finished plate after heating and firing, and therefore the wet pressed blank, the dry pressed blank and the semi-finished plate after heating and firing are all porous materials with porous structures;
[0072] Then pouring a slurry of cementitious material into the pores of the porous structure of the semi-finished plate (preferably, the semi-finished plate is first placed in a closed high-pressure tank, and then the high-pressure slurry is squeezed into the high-pressure tank for pressure pouring, so that the slurry is pressure-cast into and fills each pore, and then the semi-finished plate is fished out of the closed high-pressure tank and then cured), during the curing process, the cementitious material bonds and fixes the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles together, and the pouring and curing of the slurry of the cementitious material are similar to the cement brick manufacturing process of the prior art;
[0073] In summary, it can be summarized as follows: first, the glass fiber is heated and softened to connect, and then the cementitious material is used for secondary bonding and connection;
[0074] Here, the technical effects of this embodiment are as follows: first, due to the existence of two connections in total, namely, the heating and softening connection of the glass fiber and the secondary bonding connection of the cementitious material, two different bonding forces are provided, thereby reducing the amount of cementitious material used, thereby improving the thermal insulation performance of the thermal insulation material;
[0075] Secondly, the bonding strength generated by high-temperature heating at 650℃-800℃ is significantly higher than the bonding strength of cement and other gelling materials hardened by adding water at room temperature, and glass fiber itself is a commonly used reinforcing material. Glass fiber is similar to the steel bars in concrete. Therefore, the bonding force of high-temperature heated glass fiber strengthens the bond and connection, thereby improving the strength, hardness, tensile strength, compression resistance, bending resistance, durability and other properties of the thermal insulation material.
[0076] The present invention has no limitation on the processing equipment and process parameters not mentioned in the above method, and the processing equipment and process parameters well known to those skilled in the art can be used.
[0077] In order to further understand the present invention, a modified Class A fireproof thermal insulation material provided by the present invention is described in detail below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0078] Example 1
[0079] A modified Class A fireproof thermal insulation material is made by mixing a variety of raw materials, including the following raw materials in parts by mass: 55 parts of vitrified microspheres, 25 parts of cement, 46 parts of water, 6 parts of alumina whiskers, 8 parts of aluminum dihydrogen phosphate, 26 parts of inorganic nanoparticles, 5 parts of glass fibers, and 20 parts of inorganic aerogel powder;
[0080] The inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-alumina, with the mass of nano-silicon dioxide: the mass of nano-alumina = 1:2;
[0081] The inorganic aerogel powder is a mixture of SiO2 aerogel and Al2O3 aerogel in a mass ratio of 1:1.
[0082] A method for preparing a modified Class A fireproof thermal insulation material according to Example 1 comprises the following steps performed in sequence:
[0083] 1.1) Mixing: According to the formula, vitrified microspheres, cement, water, alumina whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder are stirred and mixed uniformly to obtain a mixed slurry;
[0084] 1.2) The prepared mixed slurry is pressed into a mold box, then solidified, and then cured to obtain a thermal insulation material.
[0085] Table 1 Performance test data of modified Class A fireproof thermal insulation material prepared in Example 1
[0086] project unit Performance Indicators Detection value density <![CDATA[kg / m 3 ]]> 160 150 Tensile strength perpendicular to the board surface MPa 0.15 0.20 Compressive strength MPa 0.20 0.35 Thermal conductivity W / (m·K) 0.030 0.029 Water absorption % ≤7 ≤6 Combustion performance grade A A
[0087] Example 2
[0088] A modified Class A fireproof thermal insulation material, made by mixing a variety of raw materials, including the following raw materials in parts by weight: 40 parts of vitrified microspheres, 38 parts of organic gelling material (melamine), 40 parts of water, 2 parts of curing agent, 5 parts of aluminum oxide whiskers, 10 parts of aluminum dihydrogen phosphate, 26 parts of inorganic nanoparticles, 6 parts of glass fibers, and 24 parts of inorganic aerogel powder;
[0089] The inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-alumina, with the mass of nano-silicon dioxide: the mass of nano-alumina = 1:1;
[0090] The inorganic aerogel powder is a mixture of SiO2 aerogel and Al2O3 aerogel, with the mass of SiO2 aerogel: the mass of Al2O3 aerogel being 2:1;
[0091] The pretreatment of the raw materials includes the following steps in sequence: in the process of producing vitrified microspheres, alumina whiskers, inorganic nanoparticles and inorganic aerogel powder are added to the vitrified microspheres when they are about to be expanded, and then the inner hollow cavity of the vitrified microspheres after expansion contains alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles, forming a structure in which particles are contained within beads.
[0092] The method for preparing a modified Class A fireproof thermal insulation material described in Example 2 comprises the following steps performed in sequence:
[0093] 1.1) Mixing: According to the formula, the glass microspheres, melamine, water, curing agent, aluminum oxide whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder are stirred and mixed uniformly to obtain a mixed slurry;
[0094] 1.2) The prepared mixed slurry is roll-formed, then solidified, and then cured to obtain a thermal insulation material.
[0095] Table 2 Performance test data of modified Class A fireproof thermal insulation material prepared in Example 2
[0096] project unit Performance Indicators Detection value density <![CDATA[kg / m 3 ]]> 150 130 Tensile strength perpendicular to the board surface MPa 0.15 0.18 Compressive strength MPa 0.20 0.26 Thermal conductivity W / (m·K) 0.030 0.027 Water absorption % ≤7 ≤5 Combustion performance grade A A
[0097] Example 3
[0098] A modified Class A fireproof thermal insulation material is made by mixing a variety of raw materials, including the following raw materials in parts by mass: 50 parts of vitrified microspheres, 22 parts of cement, 46 parts of water, 5 parts of alumina whiskers, 8 parts of aluminum dihydrogen phosphate, 30 parts of inorganic nanoparticles, 5 parts of glass fibers, and 30 parts of inorganic aerogel powder;
[0099] The inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-alumina, with the mass of nano-silicon dioxide: the mass of nano-alumina = 2:1;
[0100] The inorganic aerogel powder is a mixture of SiO2 aerogel and Al2O3 aerogel, and the mass of SiO2 aerogel: the mass of Al2O3 aerogel = 1:2;
[0101] The pretreatment of the raw materials includes the following steps in sequence: alumina whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder are stirred and mixed evenly, and then pressed into a compact, and then the compact is placed in a heating furnace for heating in an argon atmosphere (heated to 660°C-720°C and kept warm for 6 hours). During the heating process, the glass fibers are heated and softened, and the adhesiveness and adhesive force generated by the heated and softened glass fibers bond the alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fibers. Then, during the cooling process with the furnace, the alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fibers. Then, the blank obtained after heating is crushed and ground, and the particle size of the pretreated powder obtained by grinding is controlled to be 10 microns to 30 microns. The particles of the pretreated powder contain alumina whisker particles, inorganic nanoparticles, glass fibers and inorganic aerogel particles that are bonded and connected to each other.
[0102] The method for preparing a modified Class A fireproof thermal insulation material described in Example 3 comprises the following steps performed in sequence:
[0103] 1.1) Mixing: According to the formula, vitrified microspheres, cement, water, alumina whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder are stirred and mixed uniformly to obtain a mixed slurry;
[0104] 1.2) The prepared mixed slurry is pressed into a mold box, then solidified, and then cured to obtain a thermal insulation material.
[0105] Table 3 Performance test data of modified Class A fireproof thermal insulation material prepared in Example 3
[0106] project unit Performance Indicators Detection value density <![CDATA[kg / m 3 ]]> 160 155 Tensile strength perpendicular to the board surface MPa 0.20 0.25 Compressive strength MPa 0.30 0.35 Thermal conductivity W / (m·K) 0.030 0.029 Water absorption % ≤7 ≤5 Combustion performance grade A A
[0107] Example 4
[0108] A modified Class A fireproof thermal insulation material is made by mixing a variety of raw materials, including the following raw materials in parts by mass: 60 parts of vitrified microspheres, 30 parts of cement, 48 parts of water, 2 parts of alumina whiskers, 8 parts of aluminum dihydrogen phosphate, 35 parts of inorganic nanoparticles, 5 parts of glass fibers, and 30 parts of inorganic aerogel powder;
[0109] The inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-alumina, with the mass of nano-silicon dioxide: the mass of nano-alumina = 1:1;
[0110] The inorganic aerogel powder is a mixture of SiO2 aerogel and Al2O3 aerogel, and the mass of SiO2 aerogel: the mass of Al2O3 aerogel = 1:1.
[0111] The method for preparing a modified Class A fireproof thermal insulation material described in Example 4 comprises the following steps performed in sequence:
[0112] 2.1) The vitrified microspheres, half of the water, alumina whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, glass fibers and inorganic aerogel powder are mixed evenly, and then poured into a mold for pressing to form a wet-pressed slab. The aluminum dihydrogen phosphate is mixed with water to form a binder. The binder glues the vitrified microspheres, alumina whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder together to form a plate-shaped wet-pressed slab. The wet-pressed slab is then dried to form a dry-pressed slab.
[0113] 2.2) The dry pressed slab is placed in a heating furnace and heated and kept warm for a period of time in an argon atmosphere (heated to 665°C-730°C for 7 hours). During the heating process, the glass fiber is heated and softened. The adhesiveness and bonding force generated by the heated and softened glass fiber bond the glass beads, alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fiber. Then, during the cooling process with the furnace, the glass beads, alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fiber. After cooling, a semi-finished plate with a porous structure is obtained;
[0114] 2.3) The cementitious material is mixed evenly with the remaining half of the water to form a slurry, and then the slurry is poured into the pores of the porous structure of the semi-finished board. The slurry in the pores of the porous structure of the semi-finished board solidifies, and then curing is performed. During the curing process, the cementitious material bonds and fixes the glass microspheres, alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles together, and a thermal insulation material is obtained after completion.
[0115] Table 4 Performance test data of Class A fireproof modified thermal insulation material prepared in Example 4
[0116] project unit Performance Indicators Detection value density <![CDATA[kg / m 3 ]]> 180 176 Tensile strength perpendicular to the board surface MPa 0.25 0.30 Compressive strength MPa 0.40 0.50 Thermal conductivity W / (m·K) 0.050 0.040 Water absorption % ≤7 ≤5 Combustion performance grade A A
[0117] Example 5
[0118] A modified Class A fireproof thermal insulation material, made by mixing a variety of raw materials, including the following raw materials in parts by mass: 55 parts of vitrified microspheres, 30 parts of cement, 48 parts of water, 2 parts of alumina whiskers, 8 parts of aluminum dihydrogen phosphate, 33 parts of inorganic nanoparticles, 5 parts of glass fibers, and 30 parts of inorganic aerogel powder;
[0119] The inorganic nanoparticles are a mixture of nano-silicon dioxide and nano-alumina, with the mass of nano-silicon dioxide: the mass of nano-alumina = 1:3;
[0120] The inorganic aerogel powder is a mixture of SiO2 aerogel and Al2O3 aerogel, and the mass of SiO2 aerogel: the mass of Al2O3 aerogel = 1:1;
[0121] The pretreatment of the raw materials includes the following steps in sequence: alumina whiskers, inorganic nanoparticles, half of the glass fibers and inorganic aerogel powder are stirred and mixed evenly, and then pressed into a compact, and then the compact is placed in a heating furnace for heating in an argon atmosphere (heated to 660°C-730°C and kept warm for 6 hours). During the heating process, the glass fibers are heated and softened, and the adhesiveness and adhesive force generated by the heated and softened glass fibers bond the alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fibers. Then, during the furnace cooling process, the alumina whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fibers. Then, the blank obtained after heating is crushed and ground, and the particle size of the pretreated powder obtained by grinding is controlled to be 15 microns to 30 microns. The particles of the pretreated powder contain alumina whisker particles, inorganic nanoparticles, glass fibers and inorganic aerogel particles that are bonded and connected to each other.
[0122] The method for preparing a modified Class A fireproof thermal insulation material described in Example 5 comprises the following steps performed in sequence:
[0123] 2.1) The vitrified microspheres, half of the water, aluminum dihydrogen phosphate, the pre-treated powder and the remaining half of the glass fiber are mixed evenly, and then poured into a mold for pressing to form a wet-pressed slab. The aluminum dihydrogen phosphate is mixed with water to form a binder. The binder glues the vitrified microspheres, the pre-treated powder and the glass fiber together to form a plate-shaped wet-pressed slab. The wet-pressed slab is then dried to form a dry-pressed slab.
[0124] 2.2) The dry pressed slab is placed in a heating furnace and heated in an argon atmosphere (heated to 670°C-730°C and kept warm for 6 hours). During the heating process, the remaining half of the glass fiber is heated and softened. The adhesiveness and bonding force generated by the softened glass fiber bond the glass beads and the pre-treated powder to the glass fiber. Then, during the cooling process with the furnace, the glass beads and the pre-treated powder are bonded and fixed to the cooled and solidified glass fiber. After cooling, a semi-finished plate with a porous structure is obtained;
[0125] 2.3) Mix cement and the remaining half of the water evenly to form a slurry, and then pour the slurry into the pores of the porous structure of the semi-finished board. The slurry in the pores of the porous structure of the semi-finished board solidifies, and then it is cured. During the curing process, the cement bonds the vitrified microspheres and the pre-treated powder together, and the thermal insulation material is obtained after completion.
[0126] Table 5 Performance test data of modified Class A fireproof thermal insulation material prepared in Example 5
[0127] project unit Performance Indicators Detection value density <![CDATA[kg / m 3 ]]> 170 165 Tensile strength perpendicular to the board surface MPa 0.25 0.30 Compressive strength MPa 0.35 0.38 Thermal conductivity W / (m·K) 0.032 0.030 Water absorption % ≤7 ≤5 Combustion performance grade A A
[0128] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A modified Class A fireproof thermal insulation material, characterized in that: It is made of a variety of raw materials, including the following raw materials in parts by weight: 20 to 70 parts of inorganic microbeads, 15 to 40 parts of gelling materials, 30 to 50 parts of water, 1 to 8 parts of inorganic whiskers, 8 to 25 parts of aluminum dihydrogen phosphate, 20 to 35 parts of inorganic nanoparticles, 2 to 12 parts of inorganic fibers, and 20 to 50 parts of inorganic aerogel powder; The pretreatment of the raw materials includes the following steps in sequence: mixing the inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder uniformly, and then pressing them into a compact, and then placing the compact in a heating furnace for heating and heat preservation for a period of time in an argon atmosphere, the heating temperature is 650°C-800°C and the heat preservation is 5-10 hours, the glass fibers are heated and softened during the heating process, and the bonding property and bonding force generated by the heated and softened glass fibers bond the inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fibers, and then in the process of cooling with the furnace, the inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed on the cooled and solidified glass fibers, and then the blank obtained after heating is crushed and ground, and the particle size of the pretreated powder obtained by grinding is controlled to be 10 times to 20 times the particle size of the inorganic whiskers, inorganic nanoparticles or inorganic aerogel powder, and the particles of the pretreated powder contain inorganic whisker particles, inorganic nanoparticles, glass fibers and inorganic aerogel particles bonded and connected to each other; The pretreatment of the raw materials includes the following steps performed in sequence: in the process of producing inorganic microbeads, one, two or more of inorganic whiskers, inorganic nanoparticles and inorganic aerogel powders are added to the inorganic microbeads when they are about to be expanded, and then the inner hollow cavity of the inorganic microbeads after expansion contains one, two or more of inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles.
2. A modified Class A fireproof thermal insulation material according to claim 1, characterized in that: The inorganic fiber is one, two or more of glass fiber, asbestos fiber, boron fiber, aluminum silicate fiber and ceramic fiber.
3. A modified Class A fireproof thermal insulation material according to claim 1, characterized in that: The inorganic aerogel powder is one, two or more of SiO2 aerogel, Al2O3 aerogel, TiO2 aerogel, ZrO2 aerogel, Fe2O3-Al2O3 aerogel and Fe2O3-SiO2 aerogel.
4. A modified Class A fireproof thermal insulation material according to claim 1, characterized in that: The gelling material is an inorganic gelling material and / or an organic gelling material; The inorganic gelling material is one, two or more of cement, sodium silicate and silica sol; The organic gelling material is organic resin or water-based resin.
5. A method for preparing the modified Class A fireproof thermal insulation material according to any one of claims 1 to 4, characterized in that: The method includes the following steps in sequence: 1.1) Mixing: Inorganic microbeads, gelling material, water, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, inorganic fibers and inorganic aerogel powder are mixed uniformly according to the formula to obtain a mixed slurry; 1.2) The prepared mixed slurry is subjected to mold box pressing or roller pressing, and then solidified and cured, and after completion, a thermal insulation material is obtained.
6. A method for preparing the modified Class A fireproof thermal insulation material according to any one of claims 1 to 4, characterized in that: The method includes the following steps in sequence: 2.1) Inorganic microbeads, a portion of water, inorganic whiskers, aluminum dihydrogen phosphate, inorganic nanoparticles, glass fibers and inorganic aerogel powder are mixed evenly, and then poured into a mold for pressing to form a wet-pressed slab. The aluminum dihydrogen phosphate is mixed with water to form a binder. The binder glues the inorganic microbeads, inorganic whiskers, inorganic nanoparticles, glass fibers and inorganic aerogel powder together to form a plate-shaped wet-pressed slab. The wet-pressed slab is then dried to form a dry-pressed slab. 2.2) The dry pressed slab is placed in a heating furnace and heated and kept in an argon atmosphere for a period of time, and heated to 650°C-800°C for 5-10 hours. During the heating process, the glass fiber is heated and softened. The adhesiveness and bonding force generated by the heated and softened glass fiber bond the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles to the glass fiber. Then, during the cooling process with the furnace, the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles are bonded and fixed to the cooled and solidified glass fiber. After cooling, a semi-finished plate with a porous structure is obtained; 2.3) The cementitious material is mixed evenly with the remaining water to form a slurry, and then the slurry is poured into the pores of the porous structure of the semi-finished board. The slurry in the pores of the porous structure of the semi-finished board solidifies, and then curing is performed. During the curing process, the cementitious material bonds and fixes the inorganic microbeads, inorganic whisker particles, inorganic nanoparticles and inorganic aerogel particles together, and a thermal insulation material is obtained after completion.
Citation Information
Patent Citations
Aluminum silicate fiberboard and preparation method thereof
CN106747208A
Expanded microspheres and preparation method thereof
CN112321273A
Preparation method of silicon-plastic thermal insulation material
CN113185232A